METODE PERMAINAN BERCERITA EKSPRESIF PENDEKATAN MAUIDZOH UNTUK MENINGKATKAN MOTORIK HALUS DI RA BUNGA BANGSA CIREBON - Ulfah, Elis Siti Maria (Permata : Jurnal Pendidikan Agama Islam, 2024)
Early childhood playtime education for children aged 4-6 years can be implemented through media and Children aged 4–6 years are in their golden age of development, where effective learning needs to be tailored to the characteristics of children's play. Al-Qur'an education at this stage has a strategic role in instilling Islamic values, morals, and spirituality from an early age. This study aims to explore the concept and implementation of the mauizhah (wise counsel) approach in early childhood education from the perspective of the Qur’an, hadith, and educational practices in educational institutions. The issues examined include: (1) how the concept of mauizhah is understood in the Qur’an and hadith for young children; (2) how it is implemented at RA Bunga Bangsa Cirebon; (3) how effective the method of delivering mauizhah through stories, role modeling, spiritual dialogue, and instilling values is in shaping children's character; and (4) how teachers, parents, and the environment work together to educate children in accordance with the Qur'an. This study uses a descriptive qualitative approach with the main subjects being students in Group B at RA Bunga Bangsa, and secondary subjects including teachers, the school principal, and parents. The research findings indicate that the mauizhah approach integrated through expressive storytelling is effective in instilling moral values. The novelty of this study lies in the development of a Qur’anic learning model based on mauizhah that is contextual and collaborative between home and school. This approach is relevant for strengthening children’s character in modern era.